Salawat Adhiya Ulami at the Jalsatul Itsnain Baa Alawy Bandung Assembly: Salawat as a Medicine for Peace of Mind - Nurjanah , Dian Siti; Yumna; Wasik, Abdul; Hamid , Mohammad Fahmi Abdul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This paper explores the role of Salawat Adhiya Ulami in providing peace of mind to the members ofMajelis Jalsatul Itsnain Baa Alawy in Katapang, Bandung, West Java, Indonesia. This study employs aqualitative descriptive method and a phenomenological approach to uncover the life experiences of thecongregation. Data were collected through observation, interviews, and documentation, and analyzed usingqualitative analysis techniques. The findings reveal that Salawat Adhiya Ulami encapsulates the life historyof the Prophet Muhammad from birth to death and serves as a medium for expressing the congregation'slonging for the Prophet. The study highlights that, through a Sufistic approach, the act of reciting SalawatAdhiya Ulami provides a profound sense of inner peace to the congregation, fostering a belief in attaininghusnul khatimah (a good ending) in their lives. This belief is rooted in the Qur’anic verse: “O calm souls,return to your Lord, well-pleased and pleasing to Him. Enter among My servants, and enter MyParadise.” This research contributes to the study of Islamic spirituality by emphasizing the psychological andspiritual benefits of devotional practices, as well as offering a methodological insight into the use ofphenomenology in exploring religious experiences.